نحو تعريف تشغيلي للوعي ودور الضمير في العلوم الإنسانية نموذج ثلاثي الأبعاد مؤطَّر ببعد معياري (مجلة الفاروق للعلوم, 2026)
This paper proposes an operational redefinition of consciousness, shifting it from predominantly philosophical and neurological description toward an empirically examinable construct. It introduces a four-level analytical framework—cognitive perception, affective orientation, normative conscience, and practical behavior—conceiving consciousness as a dynamic and measurable process rather than a static state.Within this model, conscience constitutes the normative axis that regulates coherence among knowledge, emotion, and action. Its function is assessed through degrees of alignment: full alignment (active conscience), partial alignment (weak conscience), and total divergence (distorted conscience). These gradations allow for systematic evaluation without reducing consciousness to purely functional indicators.By positioning conscience as an evaluative core, the framework embeds consciousness within an ethical value structure while maintaining methodological rigor. This integration reconciles normative authenticity with empirical measurability, thereby offering the humanities and social sciences a structured tool for developing precise instruments of assessment. Consequently, consciousness becomes practical research variable applicable in field studies, with conscience operating as a foundational evaluative dimension.
Keywords: Consciousness, Operational framework, Cognitive perception, Normative conscience, Alignment of knowledge, emotion, and action